METHODOLOGICAL BASES OF DIFFERENTIATED CONTROL AND EVALUATION OF SPECIAL PHYSICAL AND FUNCTIONAL FITNESS OF SWIMMERS AT DIFFERENT STAGES OF LONG-TERM SPORTS TRAINING - Solopov, I.N.; Avdienko, V.B.; Fomichenko, T.G.; Bgantseva, I.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to substantiate the main provisions of the method of differentiated control and evaluation of the special physical and functional fitness of swimmers at the stages of sports training. Results and conclusions. It is noted that the diagnosis and assessment of swimmers’ preparedness should be differentiated according to the following indicators: at the initial stages of training, the assessment of preparedness should be carried out mainly in terms of morphofunctional power indicators, at the stage of sports improvement - in terms of mobilization capabilities and at the stages of higher sportsmanship - in terms of the efficiency of the functioning of all body systems. Thus, the complex control of the special physical and functional fitness of swimmers should be based on a differentiated assessment of the main, dominant factors that determine the special physical performance and, ultimately, the actual sports result, at different stages of long-term sports training and reflecting biological and physiological patterns of development of adaptability to physical activity, taking into account the individual typological characteristics of athletes and their sports specialization. It is noted that the assessment of individual indicators of swimmers, associated with the calculation of intermediate and calculated indicators, ranking and their visualization, should be automated to the maximum extent based on digital technologies.